Skills in Rheumatology - Almoallim, Hani; Cheikh, Mohamed (Springer Nature, 2021)
This Open Access book presents practical approaches to managing patients affected by various rheumatological diseases, allowing readers to gain a better understanding of the various clinical expressions and problems experienced by these patients. Discussing rheumatology from an organ systems perspective, it highlights the importance ofdetailed musculoskeletal examinations when treating patients affected by rheumatological diseases. The book first explores the latest diagnostic approaches and offers key tips for accurate musculoskeletal examinations before addressing the various treatment modalities, with a particular focus on the most common joints involved in rheumatoid arthritis: the wrists and the metacarpophalangeal joints (2nd and 3rd). Featuring easy-to-understand flow diagrams and explaining the common medical problems associated with rheumatic disease, such as shortness of breath and anemia, it is not only a valuable resource to rheumatologists, but will also appeal to medical students, junior residents, and primary healthcare physicians.